Recent Synthetic Applications of Catalyst-Free Photochemistry - Liu, Wenbo; Li, Chao-Jun (Synlett, 2017)
Catalyst-free photochemistry provides numerous opportunities toward sustainable synthesis because catalyst separation can usually be avoided, which is consistent with green chemistry principles. Complementary to the well-reviewed photoredox chemistry, this review specifically summarizes the synthetic applications of photochemistry without external catalysts reported since 2000. The selected examples include both natural product synthesis and new methodology development. This review is arranged based on the type of chromophore. It is our hope that this review will inspire more synthetic chemists to embrace photochemistry into their research plans.1 Introduction2 Photochemistry of Olefins2.1 [2+2] Cycloaddition of Enones and Olefins2.2 Cycloaddition of Olefins without Carbonyl Groups2.3 Z/E Isomerization2.4 Cyclization2.5 Others3 Photochemistry of C=O3.1 The Paternò–Büchi Reaction3.2 The Yang Photoenolization3.3 The Norrish Type I Reaction3.4 The Norrish Type II Reaction3.5 Others4 Photochemistry of Nitrogen-Containing Functional Groups5 Photochemistry of Halogen-Containing Compounds6 Conclusion and Outlook
Keywords: photochemistry; catalyst-free; organic synthesis; green chemistry